2016
DOI: 10.14260/jemds/2016/630
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Bacterial Vaginosis Among Women of Reproductive Age Attending Rural Tertiary Care Institute of Western Uttar Pradesh

Abstract: BACKGROUNDBacterial vaginosis (BV) is the most common cause of abnormal vaginal discharge among women of child bearing age and is associated with adverse obstetric and gynaecologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Prevalence of BV among women of reproductive age group is around 31.5%. Low education level and low socioeconomic status is a significant risk factor for bacterial vaginosis with 48.9% and 40.3% respectively [3]. Studies have reported a high prevalence of BV in both non-tubal and unexplained infertility [2].…”
Section: Prevalence and Association Of Bv With Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of BV among women of reproductive age group is around 31.5%. Low education level and low socioeconomic status is a significant risk factor for bacterial vaginosis with 48.9% and 40.3% respectively [3]. Studies have reported a high prevalence of BV in both non-tubal and unexplained infertility [2].…”
Section: Prevalence and Association Of Bv With Infertilitymentioning
confidence: 99%
“…The infection is characterized primarily by paucity or depletion of the vaginal lacto-bacilli and their replacement by an streptococci, and mycoplasma species [2]. Bacterial Vaginosis (BV) is the most common cause of abnormal vaginal discharge among women of child bearing age and is associated with adverse obstetric and gynecologic outcomes [3]. Common symptoms include increased vaginal discharge that often smells like fish, the discharge is usually white or gray in colour, burning with urination may occur, mild itching.…”
Section: Introductionmentioning
confidence: 99%